Assessment of Chromosome Congression Defects in Mammalian Oocytes - Horakova, Adela; Konecna, Marketa; Anger, Martin (Methods in molecular biology (Clifton, N.J.), 2025)
Congression of all chromosomes on the equatorial plane is in mitosis required for metaphase-anaphase transition, and for successful segregation of sister chromatids during anaphase. In contrast to somatic cells, mouse oocytes, which are undergoing the first meiotic division, are capable to undergo metaphase-anaphase transition without congression of all chromosomes. Consequently, oocytes exhibit an increased frequency of chromosome segregation errors, which might lead to aneuploidy. In various experimental conditions, for example, during gene function studies, or during evaluation of the effects of pharmaceutical inhibitors, it might be beneficial to assess chromosome congression in live oocytes. In this chapter, we describe all steps necessary for performing such experiments, including isolation of mouse oocytes, microinjection-free labeling of chromosomes and spindle, the time-lapse recording of chromosome division during meiosis I, using confocal live cell microscopy, and also steps necessary for data analysis.
Keywords: Animals; aparát dělícího vřeténka; Female; Meiosis; segregace chromozomů; Oocyte; ženské pohlaví; meióza; Oocytes; Time-Lapse Imaging; Live imaging; Mice; oocyty; Metaphase; myši; Chromosomes; Spindle; časosběrné zobrazování; Spindle Apparatus; zvířata; Microscopy, Confocal; konfokální mikroskopie; Chromosome Segregation; Chromosome congression